2012
DOI: 10.1126/science.1224000
|View full text |Cite
|
Sign up to set email alerts
|

Content-Specific Fronto-Parietal Synchronization During Visual Working Memory

Abstract: Lateral prefrontal and posterior parietal cortical areas exhibit task-dependent activation during working memory tasks in humans and monkeys. Neurons in these regions become synchronized during attention demanding tasks, but the contribution of these interactions to working memory is largely unknown. Using simultaneous recordings of neural activity from multiple areas in both regions, we find widespread, task-dependent and content specific synchronization of activity across the fronto-parietal network during v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
355
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(390 citation statements)
references
References 30 publications
28
355
3
4
Order By: Relevance
“…However, how the mind can manipulate these representations remains unknown. Many studies have found increased activity in frontal and parietal regions associated with a range of high-level cognitive abilities (8,9) including mental rotation (10), analogical reasoning (11), working memory (12), and fluid intelligence (13). Together, these findings suggest that a frontoparietal network may form the core of the mental workspace.…”
mentioning
confidence: 75%
“…However, how the mind can manipulate these representations remains unknown. Many studies have found increased activity in frontal and parietal regions associated with a range of high-level cognitive abilities (8,9) including mental rotation (10), analogical reasoning (11), working memory (12), and fluid intelligence (13). Together, these findings suggest that a frontoparietal network may form the core of the mental workspace.…”
mentioning
confidence: 75%
“…For two simultaneously measured time series, one is called causal to the other if the predictability of the second process at a given time point is improved by including measurements from the immediate past of the first. GC has been shown to be suitable for probing directionality in neuronal interactions for both continuous signals (26)(27)(28)(29) and spike trains (30)(31)(32). However, the pairwise approach to GC analysis may not clearly distinguish causal influences from different sources.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous recording from multiple intracortical areas in monkeys showed that the coherent higher frequency (beta and gamma bands) oscillations are linked to a broad variety of cognitive functions (12)(13)(14)(15)(16)(17)(18). Cortical oscillations at lower frequencies (theta and alpha bands) have also been discussed in terms of long-range integrative processes (19,20).…”
mentioning
confidence: 99%